The influence of indoor temperature and noise on autistic individuals - Arianna Marzi; Marco Caniato; Andrea Gasparella (Scientific Reports)
Abstract This study examines the influence of temperature and noise on autistic individuals. Conventional indoor comfort questionnaires as well as pre-validated attentional tests were administered to autistic and typically developed individuals across six different environmental scenarios. Results showed that autistic individuals struggled with completing conventional questionnaires independently providing inconsistent responses. Attentional tests were always successfully autonomously completed, revealing significant performance declines for autistic individuals because of temperature variation (4 °C) or sudden noises. Background noise (55 dB(A)) also caused performance decreases, whether typically developed individuals were unaffected by all conditions. These findings suggest that (i) conventional indoor comfort questionnaires are unsuitable for autistic individuals, (ii) indoor environmental conditions (temperature and noise) do stress autistic people (iv) stressors thresholds are provided and (iv) attentional tests could be successfully used to investigate autistic individuals’ indoor conditions and assess their perceived stress in relation to variations of temperature and acoustic circumstances.